Purwarupa RFID Student Smart Card Berbasis Raspberry pada Sekolah Menengah Kejuruan GT - Ahmad Roihan; Endang Sunandar; Muhammad Asep Abdul Fatah (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2022)
The conventional attendance system has problems and raises many questions so that administrative management becomes less effective and efficient. The focus of research is on making attendance tools an automatic attendance system by utilizing student cards as a tool to collect attendance data. Methods of collecting data were obtained by direct visits, interviews, and literature review. The analysis method is obtained by comparing the old system with the new one using the system development life cycle. The prototype method used in this research is the rapid prototyping approach. The RFID prototype for the attendance system uses student cards as a tool for attendance. So that the card becomes more useful and multi-functional. The purpose of this research is to help GT Vocational School in making a better automatic attendance system so that the system can make it easier for staff and teachers to manage attendance. The attendance system uses student cards as a tool for attendance, can make students more independent in the attendance process, and teachers just confirm on the website, and they don”t need to bring attendance papers anymore. With the automatic attendance system, all data is integrated into the website, the administrative section no longer prepares attendance papers for each teaching and learning activity.